Sodium-glucose cotransporter 2 inhibitors and type 2 diabetes: clinical pearls for in-hospital initiation, in-hospital management, and postdischarge. (March 2020) - Mazer, C. David; Arnaout, Amel; Connelly, Kim A.; Gilbert, Jeremy D.; Glazer, Stephen A.; Verma, Subodh; Goldenberg, Ronald M.
Abstract : Purpose of review: The aim of this article is to provide practical recommendations on safe initiation of sodium-glucose cotransporter 2 (SGLT2) inhibitors to in-patients as well as management of those who are already on SGLT2 inhibitors. Recent findings: Robust data from stable outpatient cohorts indicate that the SGLT2 inhibitors are associated with clinically meaningful reductions in major adverse cardiovascular events, lower rates of hospitalization for heart failure, and a reduction in major kidney outcomes There is however a lack of information on how to initiate and manage SGLT2 inhibitors in an acute in-patient setting. Summary: SGLT2 inhibitors may be cautiously appropriate for in-patients if all the criteria for safe use are met but good clinical judgment must prevail. Temporary withholding of SGLT2 inhibitors is appropriate in hospitalized patients during a period of stress and/or insulinopenia.